Features of dissipation of a powerful pulsed electron beam in high pressure gases - Sazonov R. V. Roman Vladimirovich; Novoselov Yu. N.; Kholodnaya G. E. Galina Evgenievna; Kochkorov B. Sh. Bolotbek Shakirovich; Ponomarev D. V. Denis Vladimirovich; Remnev G. E. Gennady Efimovich; Yalovets A. P.; Isakova Yu. I. Yulia Ivanovna (2010, 2010)
В фонде НТБ ТПУ отсутствует